The E3 Ligase CHIP Mediates Ubiquitination and Degradation of Mixed-Lineage Kinase 3 - Blessing, Natalya A. (American Society for Microbiology, 2014)
Mixed-lineage kinase 3 (MLK3) activates mitogen-activated protein kinase (MAPK) signaling pathways and has important functions in migration, invasion, proliferation, tumorigenesis, and apoptosis. We investigated the role of the E3 ligase carboxyl terminus of Hsc70-interacting protein (CHIP) in the regulation of MLK3 protein levels. We show that CHIP interacts with MLK3 and, together with the E2 ubiquitin-conjugating enzyme UbcH5 (UbcH5a, -b, -c, or -d), ubiquitinates MLK3 in vitro. CHIP or Hsp70 overexpression promoted endogenous MLK3 ubiquitination and induced a decline in MLK3 protein levels in cells with Hsp90 inhibition. Furthermore, CHIP overexpression caused a proteasome-dependent reduction in exogenous MLK3 protein. Geldanamycin (GA), heat shock, and osmotic shock treatments also reduced the level of MLK3 protein via a CHIP-dependent mechanism. In addition, CHIP depletion in ovarian cancer SKOV3 cells increased cell invasion, and the enhancement of invasiveness was abrogated by small interfering RNA (siRNA)-mediated knockdown of MLK3. Thus, CHIP modulates MLK3 protein levels in response to GA and stress stimuli, and CHIP-dependent regulation of MLK3 is required for suppression of SKOV3 ovarian cancer cell invasion.